2020
DOI: 10.1155/2020/8864813
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Activated Peroxisome Proliferator-Activated Receptor β/δ Facilitates Cell Proliferation in Human Cholesteatoma Keratinocytes

Abstract: Cholesteatoma is characterized by both the overgrowth of hyperkeratinized squamous epithelium and bone erosion. However, the exact mechanism underlying the hyperproliferative ability of cholesteatoma remains unknown. In this study, we investigated PPAR β/δ expression in human surgical specimens of cholesteatoma and analyzed its functional role as a regulator of epithelial keratinocyte hyperproliferation. We found that the expression of PPAR β/δ was significantly upregulated in cholesteatoma and ligand-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Literature has shown that the carcinogenesis of PPARδ was related to the activation of the PI3K-AKT pathway [ 22 , 23 ]. Therefore, we detected the expression of proteins related to the PI3K-AKT pathway in different treatment groups of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has shown that the carcinogenesis of PPARδ was related to the activation of the PI3K-AKT pathway [ 22 , 23 ]. Therefore, we detected the expression of proteins related to the PI3K-AKT pathway in different treatment groups of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated that PPARδ promoted proliferation and inhibited apoptosis through the PI3K-AKT pathway in non-small cell lung cancer [ 22 ]. Another study also revealed that PPARδ/PDK1/PTEN/AKT/GSK3β/Cyclin D1 pathway was involved in the proliferation of keratinocytes in cholesteatoma [ 23 ]. Therefore, we detected the expression of PI3K-AKT pathway related markers in agonist-intervened HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Middle ear cholesteatoma, a disease that manifests by both the overgrowth of hyper-keratinized squamous epithelium along with its aggressive clinical course with extensive bone destruction potentially resulting in severe complications, such as refractory otorrhea, balance dysfunction, vertigo, and progressive hearing loss 1 . This disease always demands surgical therapy; however, it is reported that the recidivism rate of this disease was in a wide range, from 4 to 61% 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the hypoxia status, the PI3K-Akt signaling cascade is activated in distinct cells, such pulmonary arterial smooth muscle, porcine coronary artery endothelial, A549 cells, as well as rat hepatocytes, while other cells; consisting of HEK293T, PC‑3, U373, COS‑7, and 3T3 cells do not exhibit elevated Akt phosphorylation levels 12 , 13 . Previous investigations have demonstrated that the PI3K-Akt-Cyclin D1 signaling cascade is activated in cholesteatoma epithelium and has a critical role in cholesteatoma keratinocytes hyperproliferation 1 . Previous studies revealed that hypoxia increased cell proliferation for cholesteatoma keratinocytes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…PPAR isoforms are the molecular targets of several lipid lowering and antidiabetic drugs (Berger and Moller, 2002;Atanasov et al, 2013). Previously, Zhang et al (Zhang et al, 2020). showed PPAR-β/δ isoform was upregulated in human surgical specimens of cholesteatoma which leads to proliferation of cholesteatoma keratinocytes.…”
Section: Discussionmentioning
confidence: 99%